Students' Perceptions of Using Google Translate as a Translation Tool in Writing Class - Indah Istiqomah; Ari Wibowo (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2024)
In an increasingly digitalized academic environment, the use of translation tools like Google Translate has become commonplace, especially among students in non-native English-speaking regions. This study explores students' perceptions of using Google Translate as a translation tool in writing classes within the English Education Department at UNIMUDA Sorong. Observations reveal that approximately 20 out of 30 students in the program regularly utilize Google Translate to assist with their writing assignments. This reliance is attributed to the tool's ease of use, accessibility, and ability to expedite the completion of assignments by translating ideas from Bahasa Indonesia to English. The research aims to assess how students perceive the benefits and drawbacks of using Google Translate in their academic writing. Through qualitative interviews with six randomly selected students, the study investigates their experiences with the tool, its impact on their writing quality, and its influence on their language learning process. The study highlights the convenience of Google Translate in facilitating timely submission of assignments and alleviating the challenges of vocabulary and grammar. However, it also addresses concerns regarding potential overreliance on the tool, which may undermine students' engagement with language learning fundamentals and affect the accuracy of their translated texts. Findings indicate that while students appreciate the tool’s functionality and efficiency, they acknowledge its limitations in producing contextually accurate translations. This suggests a need for a balanced approach to integrating technology in language education, where students are encouraged to use translation tools judiciously while still engaging deeply with language learning processes. The study contributes to the broader discussion on the role of digital tools in education, providing insights into students' attitudes towards Google Translate and offering recommendations for educators to support effective language development strategies.